2021
DOI: 10.1097/md.0000000000026291
|View full text |Cite
|
Sign up to set email alerts
|

Interobserver agreement and clinical disparity between the Graf method and femoral head coverage measurement in developmental dysplasia of the hip screening

Abstract: Ultrasonography is the ideal tool for assessing hip morphology in infants younger than 6-month-old. This study assessed the interobserver agreement and clinical disparities of the 2 most widely used ultrasound (US) methods, the Graf method, and femoral head coverage (FHC) measurement. A prospective observational study (STROBE compliant) of 2024 newborns was conducted between January 2017 and December 2018. Hip US was conducted on all newborns with abnormal Barlow and Ortolani maneuvers as well as on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…The earlier the DDH is detected, the better the outcome, with less complications in early phase and less likely progress to total hip replacement in adolescence or young adulthood . However, the late detection rate and the need for operative treatment are not zero with universal ultrasonographic screening either, because ultrasonography does not detect all patients with clinical instability, and the reproducibility of ultrasonographic findings varies among examiners . For example, nationwide studies from Germany and Austria presented late detected and operated rates for DDH of 0.16 to 0.26 per 1000 neonates, whereas a Swedish study reported a rate of 0.12 per 1000 neonates in clinical screening .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The earlier the DDH is detected, the better the outcome, with less complications in early phase and less likely progress to total hip replacement in adolescence or young adulthood . However, the late detection rate and the need for operative treatment are not zero with universal ultrasonographic screening either, because ultrasonography does not detect all patients with clinical instability, and the reproducibility of ultrasonographic findings varies among examiners . For example, nationwide studies from Germany and Austria presented late detected and operated rates for DDH of 0.16 to 0.26 per 1000 neonates, whereas a Swedish study reported a rate of 0.12 per 1000 neonates in clinical screening .…”
Section: Discussionmentioning
confidence: 99%
“…93,94 However, the late detection rate and the need for operative treatment are not zero with universal ultrasonographic screening either, because ultrasonography does not detect all patients with clinical instability, and the reproducibility of ultrasonographic findings varies among examiners. 95,96 For example, nationwide studies from Germany and Austria presented late detected and operated rates for DDH of 0.16 to 0.26 per 1000 neonates, whereas a Swedish study reported a rate of 0.12 per 1000 neonates in clinical screening. 84,90,97 Therefore, the cost-effectiveness of universal ultrasonographic screening should be critically assessed.…”
Section: Incidence Per 1000 Neonates (95% Ci)mentioning
confidence: 99%
“…Of 378 unique articles identified, 9 studies satisfied the prespecified inclusion criteria (Figure 2). The included studies (Table 1) were conducted between 1992 and 2021 and reported data on 50 579 hips in 27 175 infants. Information was available for both hips in 85.9% of infants.…”
Section: Resultsmentioning
confidence: 99%
“…All studies had low applicability concerns across all domains. Six studies had an unclear risk of bias in the reference standard domain because the results may have been interpreted with knowledge of the examination findings …”
Section: Resultsmentioning
confidence: 99%
“…Although the α angle, β angle, and FHC are the most common parameters in the clinical assessment of hip development in infants under 6 months of age, their accuracy and reliability remain controversial ( 5 , 6 ). Possible reasons may include inconsistent measurement methods or inherent differences in the degree of hip development.…”
Section: Introductionmentioning
confidence: 99%